Active Surveillance Cultures and Procalcitonin in Combination With Clinical Data to Guide Empirical Antimicrobial Therapy in Hospitalized Medical Patients With Sepsis - Spoto, Silvia; Daniel Markley, John; Valeriani, Emanuele; Abbate, Antonio; Argemi, Josepmaria; Markley, Roshanak; Fogolari, Marta; Locorriere, Luciana; Anguissola, Giuseppina Beretta; Battifoglia, Giulia; Costantino, Sebastiano; Ciccozzi, Massimo; et al. (Frontiers in Microbiology, 2022)
ABSTRACT Objective: The prevalence of colonization with Multidrug-Resistant Organisms (MDRO) has increased over the last decade, reaching levels as high as 23% in certain patient populations. There is a paucity of data evaluating the impact of admission Active surveillance cultures (ASC) to predict future infection. The aim of this study was to evaluate the concordance of ASC with the development of subsequent infection with the same organism in hospitalized patients (“swab-related infection”), and to describe the risk factors associated with a swab-related infection. Methods: All adults admitted to the Diagnostic and Therapeutic Medicine Department of the University Hospital Campus Bio-Medico of Rome with admission surveillance swabs (rectal or nasal) between January 2018 and February 2021 were included in the study. A retrospective chart review was conducted to identify patients that developed infections with concordant MDROs identified on ASC, and the risk factors for swab-related infection. Secondary outcomes were need of Intensive Care Unit transfer, length of stay, sepsis or septic shock development, and all-cause mortality. Results: A total of 528 patients were included in the study, of which 97 (18.3%) had a positive surveillance swab. Among patients with positive surveillance swabs, 18 (18.5%) developed an infection with a concordant organism with identical microbiological identification, 57 (58.8%) developed an infection with a pathogen unique to that detected by surveillance swab, and 22 (22.7%) did not develop an infection during hospitalization. The number of colonized sites, an interventional procedure within the previous three months, a Systemic Inflammatory Response Syndrome (SIRS) score ≥ 2, and a quick Sequential Organ Failure Assessment (q-SOFA) score ≥ 2 were associated with a significantly higher risk of developing a swab-related infection. SIRS and q-SOFA scores ≥ 2 and Procalcitonin ≥ 0.43 ng/mL help in identify patients with a swab-related infection. Conclusion: This study is the first showing that the positivity of surveillance swabs, in combination with anamnestic data, PCT values, and SIRS or q-SOFA scores, predict patients at higher risk for swab-related infection development and guide the administration of appropriate empiric antimicrobial therapy in septic patients.